Persons unknown : a novel - Steiner, Susie, 1971- (Random House, 2017)
"Detective Manon Bradshaw is five months pregnant and has officially given up on finding romantic love. Instead, she is in hot-pursuit of the work-life balance and parked in a cold case corridor--the price she's had to pay for a transfer back to Cambridgeshire. This is fine, she tells herself. She can devote herself to bringing up her motley collection of children--the new baby, and her adopted 12-year-old son Fly Dent. He needed a fresh start--he was being forever stopped and searched in London by officers who couldn't see past the color of his skin. Manon feared Fly, increasingly sullen and adolescent, was getting in with the wrong crowd at school, or possibly that he was the wrong crowd. Yes, children, home-cooked food, home by five. This is what I need, she tells herself. Yet when a well-to-do victim is found stabbed close to police HQ, she can't help but sidle in on the briefing. It emerges he is a banker from London, worth millions, called Jon-Oliver Ross. More dramatically, Ross was Manon's sisterEllie's ex, and the father of her toddler son, Solomon. The investigation swirls with greater and greater urgency, and as it begins to circle in on Manon's home and her family, she finds herself pitted against the former colleagues she once held dear--Davy Walker and Harriet Harper. Can Manon separate what she knows about the people she loves, from the suspicion hanging over them? Can she interrogate the evidence, just as she would with any other case? And when Manon instructs defence lawyer Mark Talbot to work alongside her, can she refrain from throwing herself at him in a manner unbecoming to a woman at an advanced stage of pregnancy? Manon must fight to find the truth with every fiber of her being, and this might just finish her"--